The Roots of Rough Justice : Origins of American Lynching - Pfeifer, Michael J. (Michael James), 1968- (Book collections on Project MUSE., 2011)
In this deeply researched prequel to his 2006 study 'Rough Justice: Lynching and American Society, 1874-1947', Pfeifer analyzes the foundations of lynching in American social history.